Spontaneous intestinal perforation in extremely low birth weight infants: association with indometacin therapy and effects on neurodevelopmental outcomes at 18–22 months corrected age. Issue 2 (9th June 2012) - Wadhawan, Rajan; Oh, William; Vohr, Betty R; Saha, Shampa; Das, Abhik; Bell, Edward F; Laptook, Abbott; Shankaran, Seetha; Stoll, Barbara J; Walsh, Michele C; Higgins, Rose
Abstract : Background: Spontaneous intestinal perforation (SIP) is associated with the use of postnatal glucocorticoids and indometacin in extremely low birth weight (ELBW) infants. The authors hypothesised: 1) an association of SIP with the use of antenatal steroids (ANS) and indometacin either as prophylaxis for intraventricular hemorrhage (IVH) (P Indo) or for treatment of PDA (Indo/PDA) and 2) an increased risk of death or abnormal neurodevelopmental outcomes in infants with SIP at 18–22 months corrected age. Design/Methods: The authors retrospectively identified ELBW infants with SIP in the Neonatal Research Network's generic database. Unadjusted analysis identified the differences in maternal, neonatal and clinical variables between infants with and without SIP. Logistic regression analysis identified the adjusted OR for SIP with reference to ANS, P Indo and Indo/PDA. Neurodevelopmental outcomes were assessed among survivors at 18–22 months corrected age. Results: Indo/PDA was associated with an increased risk of SIP (adjusted OR 1.61; 95% CI 1.25 to 2.08), while P Indo and ANS were not. SIP was independently associated with an increased risk of death or neurodevelopmental impairment (NDI) (adjusted OR 1.85; 95% CI 1.32 to 2.60) and NDI among survivors (adjusted OR 1.75, 95% CI 1.20 to 2.55). Conclusion: Indometacin used for IVH prophylaxis and ANS were not associated with the occurrence of SIP in ELBW infants. Indometacin used for treatment of symptomatic PDA was however associated with an increased risk of SIP. ELBW infants with SIP have an increased risk of poor neurodevelopmental outcomes.